Pudendal Nerve Block in Hemorrhoid Surgery: A Systematic Review and Meta-analysis. Issue 5 (10th February 2021) - Mongelli, Francesco; Treglia, Giorgio; La Regina, Davide; Di Giuseppe, Matteo; Galafassi, Jacopo; Majno-Hurst, Pietro E.; Christoforidis, Dimitrios
Abstract : BACKGROUND: Postoperative pain represents an important issue in traditional hemorrhoidectomy. Optimal pain control is mandatory, especially in a surgical day care setting. OBJECTIVE: The aim of this study was to investigate the use of pudendal nerve block in patients undergoing hemorrhoidectomy. DATA SOURCES: PubMed, Google Scholar, Cochrane Library, and Web of Science databases were searched up to December 2020. STUDY SELECTION: Randomized trials evaluating the pudendal nerve block effect in patients undergoing hemorrhoidectomy were selected. INTERVENTIONS: Hemorrhoidectomy under general or spinal anesthesia with or without pudendal nerve block was performed. MAIN OUTCOME MEASURES: Opioid consumption, pain on the visual analogue scale, length of hospital stay, and readmission rate were the main outcomes of interest and were plotted by using a random-effects model. RESULTS: The literature search revealed 749 articles, of which 14 were deemed eligible. A total of 1214 patients were included, of whom 565 received the pudendal nerve block. After hemorrhoidectomy, patients in the pudendal nerve block group received opioids less frequently (relative risk, 0.364; 95% CI, 0.292–0.454, p < 0.001) and in a lower cumulative dose (standardized mean difference, –0.935; 95% CI, –1.280 to –0.591, p < 0.001). Moreover, these patients experienced less pain at 24 hours (standardized mean difference, –1.862; 95% CI, –2.495 to –1.228, p < 0.001), had a shorter length of hospital stay (standardized mean difference, –0.742; 95% CI, –1.145 to –0.338, p < 0.001), and had a lower readmission rate (relative risk, 0.239; 95% CI, 0.062–0.916, p = 0.037). Sensitivity analysis excluded the occurrence of publication bias on the primary end point, and the overall evidence quality was judged "high." LIMITATIONS: Occurrence of publication bias among some secondary end points and heterogeneity are the main limitations of this study. CONCLUSIONS: This systematic review and meta-analysis show significant advantages of pudendal nerve block use. A reduction in opioid consumption, postoperative pain, complications, and length of stay can be demonstrated. Despite the limitations, pudendal nerve block in patients undergoing hemorrhoidectomy should be considered.